Аналіз криміналістичної інформації про вчинення кримінальних правопорушень у сфері господарської діяльності, вчинених за допомогою підроблених документів - Жердєв, В. К.; Zherdiev, V. K. (Юридичний науковий електронний журнал. - 2023. - № 2. - С. 472-474, 2023)
Здійснено аналіз криміналістичної інформації про вчинення кримінальних правопорушень у сфері господарської діяльності вчинених за допомогою підроблених документів. Зазначено, що існує два види підроблення документів: інтелектуальне і матеріальне. Інтелектуальне підроблення полягає в складанні і видачі документа, правильного з формальної сторони (наявність і правильність усіх реквізитів), але дані, вказані в ньому є завідомо неправдивими. При матеріальному підробленні вносяться зміни до змісту справжнього документа. Матеріальне підроблення документів поділяють на два види: повне підроблення та часткове підроблення. Розглянуто, який предметів фальсифікації, використовуються при здійсненні незаконної господарської діяльності. Узагальнено, що типовими способами приховування ведення незаконної господарської діяльності є: відсутність документів, передбачених законом для певного виду ведення господарської діяльності; ведення неофіційного обліку, так званої «подвійної бухгалтерії», а також видача неоформленої винагороди за працю «зарплати в конвертах». Наголошено, що підроблення документів у сфері господарської діяльності має зв’язок з певними складовими економіки: власністю, виробництвом, використанням трудових ресурсів та/або розрахунків.

The article analyzes forensic information on the commission of criminal offenses in the field of economic activity committed with the help of forged documents. From the analysis of the investigative practice of the National Police of Ukraine, it was established that most often the facts of the use of falsification of documents related to the commission and concealment of criminal offenses provided for by Art. 205-1, 212, 218-1, 220-1, 223-1, 357, 358 of the Criminal Code of Ukraine. It is noted that there are two types of forgery of documents: intellectual and material. Intellectual forgery consists in drawing up and issuing a document that is correct on the formal side (the presence and correctness of all details), but the data specified in it are known to be false. In the case of material forgery, changes are made to the content of a genuine document. Material forgery of documents is divided into two types: full forgery and partial forgery. It has been considered which items of falsification are used in the implementation of illegal economic activity. Examples are given. In general, the typical methods of concealing the conduct of illegal economic activity are: lack of documents provided by law for a certain type of economic activity; keeping unofficial records, the so-called «double bookkeeping», as well as issuing unregistered remuneration for work «salaries in envelopes». Based on research, it was concluded that forgery of documents in the field of economic activity is related to certain components of the economy: property, production, use of labor resources and/or calculations. The detection of such forensic information is facilitated by the analysis of a complex of factors that go beyond the scope of evidence in criminal proceedings (about the economic, industry, corruption situation of counterfeiting). The considered information, depending on its impact on a specific operational, expert or investigative situation, has a different potential for its further use in an operational or criminal process.

Проведен анализ криминалистической информации о совершении уголовных правонарушений в сфере хозяйственной деятельности совершенных с помощью поддельных документов. Отмечено, что существует два вида подлога документов: интеллектуальный и материальный. Интеллектуальный подлог заключается в составлении и выдаче документа, правильного с формальной стороны (наличие и правильность всех реквизитов), но данные, указанные в нем заведомо ложны. При материальном подлоге вносятся изменения в содержание настоящего документа. Материальный подлог документов разделяют на два вида: полный подлог и частичный подлог. Рассмотрено, какие предметы фальсификации, используются при осуществлении незаконной хозяйственной деятельности. Обобщено, что типичными способами сокрытия ведения незаконной хозяйственной деятельности есть: отсутствие документов, предусмотренных законом для определенного вида ведения хозяйственной деятельности; ведение неофициального учета, так называемой «двойной бухгалтерии», а также выдача неоформленного вознаграждения за труд «зарплаты в конвертах». Подчеркнуто, что подделка документов в сфере хозяйственной деятельности имеет связь с определенными составляющими экономики: собственностью, производством, использованием трудовых ресурсов и/или расчетов.
Analysis of forensic information on the commission of criminal offenses in the field of economic activity committed with the help of forged documents
Жердєв, В. К. Аналіз криміналістичної інформації про вчинення кримінальних правопорушень у сфері господарської діяльності, вчинених за допомогою підроблених документів [Електронний ресурс] / Жердєв В. К. // Юридичний науковий електронний журнал. - 2023. - № 2. - С. 472-474. – Режим доступу: http://www.lsej.org.ua/2_2023/111.pdf.
Keywords: Криміналістика. Criminalistics. Криминалистика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; криміналістична інформація; forensic information; криминалистическая информация; підроблення документів; forgery of documents; подделка документов; кримінальні правопорушення у сфері господарської діяльності; criminal offenses in the field of economic activity; уголовные правонарушения в сфере хозяйственной деятельности